UPAYA PREVENTIF TERHADAP KELUHAN MUSCULOSKELETAL SELAMA MASA PANDEMI PADA PETANI DI KAMAL WETAN - fitri yani; Nurwahida Puspitasari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Farmers as one of the informal sector workers in Indonesia have experienced various health problems. Health problems that often occur are malnutrition, chemical poisoning, intestinal worms, food poisoning, muscle and bone disorders, asthma, respiratory disorders, and even blood diseases. The purpose of this community service is to provide preventive efforts for farmers to maintain physical health in the midst of a pandemic. physical activity education that can be done at home to increase body immunity. This activity consists of counseling related to musculoskeletal complaints and how to prevent them. In addition to the socialization, it also provides education on how to carry out occupational health and safety for farmers. Furthermore, it is hoped that by providing this socialization, farmers are more aware of occupational health and safety during farming.   Keywords: Preventive Measures, Musculoskeletal Complaints, Farmers